Democracy and exclusion - Lenard, Patti Tamara, 1975- (Oxford University Press, 2023)
"As people become more mobile, the nature of citizenship, and all its attendant rights, has become the object of intense scrutiny. And, as we know, democracies forcefully and coercively exclude those whom they believe do not belong on their territory or among their constituency. This book looks at how and when democracies exclude both citizens and non-citizens from territory and from membership to determine if and when these instances are justified. This book draws on the all-subjected principle—the idea that all those who are the subject of law—should have a real say in what the law is. This principle rarely supports exclusion, and instead shows that in most cases admission—to territory and membership—is either favored by, or required by, democratic justice. Using a contextual methodology and taking for granted that states have at least some rights to control their borders, this book considers a wide range of cases to demonstrate how a focus on subjection can illustrate who merits inclusion, usually in the form of citizenship status. Among the cases considered are stateless peoples, foreign fighters, and their children, convicted and suspected terrorists domestically and abroad, those fleeing humanitarian disasters, resettled refugees, asylum seekers, and temporary labor migrants. The book concludes with a consideration of the way in which systemic racism and discrimination, including through the adoption of policies that deliberately target racial, cultural, and ethnic minorities make their inclusion as full and equal members of democratic communities a struggle"--Publisher's description.